The determinants of capital structure for construction firms listed in Bursa Malaysia / Muhammad Imran Arif Mohd Nasir - Mohd Nasir, Muhammad Imran Arif (Faculty of Business Management, 2017)
Factors that affect failure of firms are bad financial management and lack of capital. The construction industry is facing these problems. A study by (Adnan Enshassi, 2006) finds that construction companies have high business failure rate compare to other sectors. . For further better management of capital, this research is conducted to determine factors that affected capital structure for construction companies listed in Bursa Malaysia. This study examines the capital structure for the construction companies listed in Bursa Malaysia market during a five-year period from 2012-2016. This sample data derived from financial statements of 25 companies with number of observations is 125. The dependent variable is debt ratio (total debt/total assets) while independent variables are profitability (earnings before interests and taxes/total assets), size (natural logarithm of total assets), growth (market-to-book ratio) and assets tangibility (total fixed assets/total assets). The method used in this study is Pooled Ordinary Least Square (OLS). The expected results of this study are profitability and growth are significant negative to debt ratio while size and assets tangibility are positively significant to debt ratio.